55 Use of sirolimus coated balloon in de novo small vessel coronary lesions in acute coronary syndrome; long-term follow-up from a single centre registry. (6th June 2022) - Zakai, Maria; Loku Waduge, Bhagya Harindi; Kumar, Nitin; Ment, Jerome; Freestone, Bethan; Pitt, Michael; Bhatia, Gurbir; Athukorala, Sampath; Lee, Kaeng; Pulikal, George; Basavarajaiah, Sandeep
Abstract : Background: Drug coated balloons (DCBs) are mainly used in restenotic lesions as endorsed by the European Society of Cardiology, with a class IA recommendation. However, some of the recent data suggest, it can also be considered in a subset of denovo lesions. In this study, we report outcomes from the use of a Sirolimus coated balloon (SCB) in de novo small-vessel coronary lesions specifically in the context of acute coronary syndrome (ACS), from a high volume centre. Methods: A retrospective analysis was conducted on all patients treated with an SCB for ACS between March 2018 and October 2020. Follow-up was achieved with clinic visits, telephone calls and admission records. The outcomes measured include cardiac death, target-vessel myocardial-infarction, target lesion revascularisation and MACE (combination of cardiac death, target-vessel MI and TLR). Results: During the study period, 289-patients (401 lesions) were treated with an SCB for de novo small vessel lesion in ACS, of which 20% were STEMIs (n= 59) with the remainder being NSTEMIs (n=230) and there were 319 NSTEMI lesions and 82 STEMI lesions treated. The mean age of patients was 65 years (range 37–97), 81 (55%) were male, 41% (n=119) had diabetes, 73% (n= 210) had hypertension and 21% (n=59) had chronic kidney disease. Pre-dilatation was performed in 98% lesions (n = 394) and bailout stenting (with DES) was required in 3.2% of lesions (n=13). The mean diameter and length of DCBs were 2.78 mm and 26 mm respectively. During a median follow-up 570 days (19 months), cardiac death was reported in 8 patients (3%). Target vessel MI was in 7% (n=19), TLR per lesion was 12% (n=48) and the MACE rate was 14% (n=41). There were no documented cases of acute vessel closure. Conclusion: The long-term outcome from the first ever study on sirolimus eluting balloon in de novo small vessel lesions in ACS appears promising with low rates of hard endpoints and acceptable TLR. This study suggests that use of SCB in de novo small vessel lesions in ACS may be reasonable therapeutic option. Conflict of Interest: None